Science Teaching Materials Based on Multiple Intelligences - Arrofa Acesta (Universitas Pendidikan Ganesha, 2023)
The problem in this research is that there need to be science teaching materials based on multiple intelligences and low science learning outcomes. This study aims to produce appropriate multiple intelligences-based science teaching materials and know the effectiveness of science teaching materials based on multiple intelligences. This type of research is development research which refers to the ADDIE development model. Methods of data collection using a questionnaire. The research instrument used was a questionnaire in the form of validity and practicality sheets; the validation sheet was filled in by material experts, learning design experts, and teachers, while fourth-grade students carried out the student effectiveness test. The data collected from the questionnaire results were analyzed using quantitative description analysis techniques. The results showed that the material expert validation included the very feasible category of 89.67%. The validation of category learning design experts is very feasible, 91%. The teacher validation results are in the proper category at 79.20%. Based on the results of limited trials of multi-intelligence-based science teaching materials, teachers and students believe it is suitable for use in class IV and for independent learning. It was concluded that science teaching materials based on multiple intelligences were appropriate for learning.